Impact of Levothyroxine Therapy on Pregnancy Outcomes in Anti-TPO Positive Women with Subclinical Hypothyroidism: A Prospective Multi Centers Study - Khalid Usman, Rab Nawaz Khan, Sahibzada Imtiaz Ahmad, Saleh Ahmad, Kifayat Ali, Tahir Ghafar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There are undesirable maternal and fetal consequences of subclinical hypothyroidism in pregnant women, particularly those with anti-thyroid peroxidase (Anti-TPO) antibodies. The earlier a patient is diagnosed, and treated may result in better outcomes of pregnancy but there is still less data concerning the effectiveness of treatment in those who are positive with anti-TPO. This study will assess the impact of treatment in this particular group in terms of changes in pregnancy. Objectives: To determine the outcomes of such treatment of pregnant women with subclinical hypothyroidism who’s Anti-TPO screen was positive and to evaluate the treatment effect of thyroid hormones on the health indicators of the mother and child. Stud design: A Prospective Multi Centers Study. Place and Duration of Study: Department of Endocrinology, MTI-HMC Peshawar; Timergara Teaching Hospital, Timergara and the District Headquarter Hospital, Dir Upper from Jan 2020 to Jan 2023 Methods: This prospective Multi centers study was conducted in the Department of Endocrinology, MTI-HMC Peshawar; Timergara Teaching Hospital, Timergara and the District Headquarter Hospital, Dir Upper from Jan 2020 to Jan 2023. The study involved 100 women diagnosed with subclinical hypothyroidism and positive anti-thyroid peroxidase (Anti-TPO) antibodies. Participants were administered levothyroxine treatment and monitored throughout pregnancy. Serum samples were collected to assess pregnancy-related complications, thyroid function parameters, and neonatal outcomes at three months postpartum. Data analysis was performed using a statistical software program, with a significance level set at p < 0.05. Means, standard deviations, and p-values were calculated for both treated and untreated groups. Result: 100 pregnant women subclinical hypothyroidism and positive Anti-TPO antibodies. Mean age was 28.5 + 4.2 years old. The treated patients had a statistically better thyroid response with sharp improvements in the level of TSH through the second trimester (p = 0.003). The incidences of pregnancy related complications including preterm births and miscarriage were also lower in the treated group than the untreated control group ( p = 0.01). Neonatal outcomes such as birth weight and Apgar scores were improved in the treated group which was found to be significantly different (p=0.02). These findings imply that maternal and neonatal health were improved by treatment. Conclusion: Levothyroxine therapy in anti-TPO positive pregnant women with subclinical hypothyroidism significantly reduces pregnancy-related morbidity. Early detection and timely treatment are crucial to improving both maternal and fetal outcomes. Routine screening and management of subclinical hypothyroidism during pregnancy are recommended, particularly in patients with positive anti-TPO antibodies, as they tend to have more favorable outcomes with treatment. Keyword: Subclinical hypothyroidism, pregnancy, anti-TPO, levothyroxine